Influence of Velocity on Heat Transfer Performance of Ribbed Channels: A Numerical Study - Đặng Thị Tường Vi; Trần Thanh Tình; Đặng Thành Trung (Journal of Technical Education Science, 2025)
To evaluate the effect of velocity on the thermal performance of the ribbed channel (used as a cooling channel in turbine blades), this study performed numerical investigation using the Ansys Fluent 19.2 software. The investigated velocity range from 2.8 m/s to 11.2 m/s (corresponding to Reynolds number from 10,217 to 40,867) showed that increasing velocity reduces the thermal boundary layer and enhances the mixing of the cooling air flow, thereby improving the heat transfer capacity. However, increasing velocity also increases the pressure loss in the channel, including local losses at the ribs. Based on the simulation results, the empirical coefficients C = 11.648 and n = 0.3986 were determined for the correlation equation of Nusselt number (Nu) against Reynolds number (Re) for air. These results are the premise for the next research steps when studying to improve the heat exchange capacity with ribs by changing the inlet flow parameters.